Understanding the experience of nursing students' internship at a palliative care unit: A phenomenological research study. (May 2021) - Farfán-Zúñiga, Ximena; Jaman-Mewes, Paula
Abstract: Background: Palliative care is characterised as a holistic, interdisciplinary and humanised approach to care. It transcends the traditional bio-medical perspective in health through a bio-psycho-social and spiritual approach. Holistic point of view in palliative care is essential, and needs to be consistently hi-lighted to nursing students to improve end of life care. Objective: To describe nursing students' experience in a palliative care unit in Santiago, Chile. Design: A qualitative phenomenological study utilising purposive sampling of 10 nursing students from a Chilean university was undertaken, who completed their final year in a palliative care unit between 2017 and 2019. Methods: Data were collected using in-depth interviews, which were conducted, recorded, transcribed and analysed according to Streubert-Carpenter method. This study was approved by the Ethics Committee of Universidad de los Andes, Chile. Results: Three main themes were identified in the data with their consequent units of meaning; these were experiences from all participants. The first theme identified was the diverse learning experiences students had. Topics included were: spirituality, dignity, teamworking and communication with the patient and family. They also identified personal growth. The second theme was living through the experience of difficult times; this included how they dealt facing death and how they found meaning on this. Also, patient loneliness, abandonment and the impact of shortage of human and material resources. The final theme was recognising that touching patients is often the essence of nursing and is paramount in palliative care. Conclusions: Completing a placement in a palliative care unit contributes to student nurses' personal and professional development. It provides multiple tools related to the care of terminally-ill patients and their families. It is recommended to undergraduate nurses have the opportunity to experience palliative care throughout curriculum and that they learn to embed theory to practice.